Analisis Harga Dan Cita Rasa terhadap Loyalitas Pelanggan yang Dimediasi oleh Kepuasan Pelanggan Minuman Teh dalam Kemasan Siap Minum Merek Teh Botol Sosro di Kota Bandung - Nadila Octa Nuraini; Tania Adialita (IPM2KPE, 2024)
This research aims to analyze the impact of price and taste on customer loyalty, with customer satisfaction as a mediator, in ready-to-drink packaged tea drinks under the Teh Botol Sosro brand in Bandung City. The research method uses a quantitative approach with surveys and Likert questionnaires. The research instrument has gone through the validity, reliability, descriptive analysis, classical assumptions, multiple regression and Sobel test stages. Data was collected from 120 respondents aged at least 17 years who had consumed Teh Botol Sosro at least twice a month. The analysis results show that price and taste positively influence customer satisfaction, while taste and customer satisfaction have a positive influence on loyalty. However, customer satisfaction does not act as a mediator between price, taste and customer loyalty. In conclusion, price and taste have a direct influence on the satisfaction and loyalty of Teh Botol Sosro customers in Bandung City. Keywords: Taste, Price, Customer Satisfaction, Customer Loyalty